Supernumerary teeth in the midline, an interesting case for clinical practice - Lianne Laura de León Ramírez; Damarys Calvo Pérez; Marisel García del Busto Chinea; Liliana Abreu Pachón (Universidad de Ciencias Médicas de Granma, 2023)
Introduction: sometimes patients with supernumerary teeth come to the dental clinic. For this reason, knowledge of the morphological characteristics of each dental group is useful to differentiate them from those of the normal arch. Case Presentation: the case of an apparently healthy 12-year-old male patient who attended the Maxillofacial Surgery service, referred from Primary Health Care for the extraction of "a supernumerary" was presented. Upon questioning, the mother stated that the child received orthodontic care around eight years of age and that under this treatment he was indicated and performed surgery "because he had an extra tooth." Once the case was assessed, the presence of two supplementary supernumeraries in the maxillary midline was diagnosed. The tooth that had been extracted during the previous orthodontic treatment, referred by the mother, was the upper left central incisor (21) and not a supernumerary. The ectopic 11 was extracted, to leave in the dental arch the two supernumeraries that were of similar anatomy and were completely erupted. Conclusions: supernumerary teeth of the midline, when they have anatomical characteristics similar to those that normally occupy the dental arch, can be confused with these; hence the importance of a thorough clinical assessment.